Celiac disease: is it really possible to overcome duodenal biopsy? - Grande, Elisabetta; Ferranti, Silvia; Gaggiano, Carla; di Virgilio, Nicola; Vascotto, Marina (Acta Biomedica Atenei Parmensis, 2016)
We report the case of a two-year-five-month-old child who underwent screening for celiac disease due to strong familiarity. During the first observation body weight and height were at 25th and 50th centile for gender and age. Physical examination did not reveal any sign of disease. Blood tests showed increased transaminases levels and antibodies research showed: tTG IgA: 100 UI/ml, tTG IgG: 36,6 UI/ml, EMA IgA: positive. HLA study revealed homozygous allelic combination DRB1*07;DQA102:01; DQB1* 02:02 with presence of a double copy of beta chain in the composition of the  DQ2 heterodymer. Biopsy with histological examination did find neither mucosal alteration  nor lymphocytic infiltrates (Marsh 0). During follow up with free diet the patient remained asymptomatic and all antibody titers decreased up to normalization. According to ESPGHAN guidelines the finding of hypertransaminasemia as sign of celiac hepatic inflammation, a more than 10-fold increase of tTG IgA and a high-risk HLA would permit diagnosis of celiac disease but histological examination done due to mismatch between paucity of clinical sings and a “multiple risk combination” excluded it, allowing diagnosis of potential celiac disease.  We believe that this case is interesting because of its being in contrast with current literature data that suggest a linear relationship between antibodies levels and histological damage with tTG IgA at the upper reference range in case of potential celiac disease. According to guidelines we could have avoided intestinal biopsy but we would have considered as celiac a patient who is maybe just potentially affected.